2020
DOI: 10.1093/femsec/fiaa235
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptome analysis of Rhizobium favelukesii LPU83 in response to acid stress

Abstract: Acidic environments naturally occur worldwide and inappropriate agricultural management may also cause acidification of soils. Low soil pH values are an important barrier in the plant-rhizobia interaction. Acidic conditions disturb the establishment of the efficient rhizobia usually used as biofertilizer. This negative effect on the rhizobia-legume symbiosis is mainly due to the low acid-tolerance of the bacteria. Here, we describe the identification of relevant factors in the acid tolerance of Rhizobium favel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 93 publications
1
4
1
Order By: Relevance
“…OR191 produced 0.1 mg ml –1 and 0.5 mg ml –1 EPS at pH 7.0 and 5.8, respectively, representing a fivefold increase in EPS production in acidic conditions. This differs from previous reports of EPS production in R. favelukesii LPU83 T , which found no significant difference in the amount of EPS obtained from cells grown under neutral and acidic conditions ( Nilsson et al, 2020 ). In contrast, the E. medicae strain WSM419 produced 0.05 mg ml –1 and 4.65 mg ml –1 EPS at pH 7.0 and 5.8, respectively, representing a 93-fold increase in EPS production in acidic conditions.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…OR191 produced 0.1 mg ml –1 and 0.5 mg ml –1 EPS at pH 7.0 and 5.8, respectively, representing a fivefold increase in EPS production in acidic conditions. This differs from previous reports of EPS production in R. favelukesii LPU83 T , which found no significant difference in the amount of EPS obtained from cells grown under neutral and acidic conditions ( Nilsson et al, 2020 ). In contrast, the E. medicae strain WSM419 produced 0.05 mg ml –1 and 4.65 mg ml –1 EPS at pH 7.0 and 5.8, respectively, representing a 93-fold increase in EPS production in acidic conditions.…”
Section: Resultscontrasting
confidence: 99%
“…The olsC gene, which has been identified as being important for the production of hydroxylated ornithine lipid species that increase stress tolerance in CIAT899 T ( Rojas-Jiménez et al, 2005 ; Vences-Guzmán et al, 2011 ), was present in both the highly acid tolerant strain R. tropici CIAT899 T and in R. favelukesii strains but was absent from E. medicae WSM419 and E. meliloti 1021. This accords with proteomic and transcriptomic studies of R. favelukesii LPU83 T that revealed changes in proteins and genes associated with lipid metabolism involving the cell envelope in response to acid stress, however, these studies also suggested that some acid-responsive regulatory systems differ in LPU83 T compared with Ensifer strains ( Nilsson et al, 2019 , 2020 ).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Secreted EPS are increased under abiotic stress (Hirsch, 1996;Sorroche et al, 2018;Primo et al, 2020). However, at acid pH R. tropici CIAT899 showed a lower production of biopolymers (Avelar Ferreira et al, 2012), whereas EPS production was not affected in R. favelukesii LPU83 (Nilsson et al, 2021).…”
Section: Importance Of Exopolysaccharides Production In Symbiosismentioning
confidence: 96%
“…In fact, only a few studies have indicated the potential of microalgae as biofertilizers in soil microcosm experiments. , Only a few studies have discussed the microbial community structure and function in soils associated with various acidification units . Very recently, Nilsson et al reported that acid conditions are an important barrier in plant–rhizobia interaction, and it disturbs the establishment of efficient rhizobia used as biofertilizers. We used two acid-tolerant microalgal strains, Desmodesmus sp.…”
Section: Introductionmentioning
confidence: 99%